SPECIFIC SOLUTIONS OF ODE SYSTEM FOR MODELING STATIONARY COMPRESSIBLE FRICTION FLOW OF PERFECT GAS IN CONSTANT-AREA CHANNEL - Fedorov, M. (Proceedings of National Aviation University (archive), 2021)
In the paper some specific solutions of the general solution taken in [1 ] are considered to model a one-dimensional stationary flow of a compressible gas in the constant-area channel. New analytical solutions and interpretations of the known ones are given.